AUDIT MANAJEMEN UNTUK MENILAI EFEKTIVITAS FUNGSI SUMBER DAYA MANUSIA (Studi Kasus Pada PT. Pura Barutama) - Wahyuni Nur Hidayati; Nurul Fachriyah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Management audit of human resource at PT. Pura Barutama aims to knowhow effective of human resources at PT. Pura Barutama and identify weaknessesand give recommendation for these weaknesses. Research method used isdescriptive method with a case study approach. The method used for collect dataare interview, documentation, questionnaire and observation. Data analyzingprocess use qualitative analysis method which is grouping the findings into 4(four) categories, that are criteria, condition, cause, effect. This procces is carriedout to know how succeed the company develop the human resource. Audit scopediscussed in this research cover 11 (eleven) functions, which are (1) humanresource planning, (2) recruitment, (3) selection and orientation, (4) training anddevelopment, (5) career planning and development, (6) perfomance assesment, (7)compensation, (8) protection and occupational health, (9) job satisfaction, (10)company and employee relationship, (11) work termination.Based on this research result, most of the human resource function at PT. PuraBarutama are effective in accordance with applicable policy and regulation.There are 8 (eight) functions that already effective, which are human resourceplanning, recruitment, selection and orientation, career planning anddevelopment, perfomance assesment, job satisfaction, company and employeerelationship, and work termination. Three functions that may not be effective aretraining and development, compensation, and protection and occupational health.Based on the weaknesses found, the author gives some recommendations andimprovements to be used by PT. Pura Barutama as consideration in humanresources management.Keywords: Management audit, human resources function, effectiveness,criteria, cause, effect, recommendation